PENERAPAN KONSEP ARSITEKTUR BIOPHILIC PADA FASILITAS PENGOLAHAN LIMBAH ORGANIK DI KAWASAN PASAR KEBAYORAN LAMA - Tandjung, Michael Emmanuel; Surya, Rudy (Jurusan Arsitektur dan Perencanaan, 2025)
Environmental problems caused by the accumulation of organic waste, particularly in traditional market areas, have become a crucial issue that requires sustainable solutions. A significant increase in organic waste production has occurred in the Kebayoran Lama Market area due to the high level of activity in the area, which generates large amounts of organic waste every day. Most organic waste is disposed of directly without undergoing effective processing, thereby increasing the environmental burden. This study examines the application of biophilic architecture concepts in organic waste processing facilities in the Kebayoran Lama Market area as an effort to create processing spaces that are not only functional but also have a positive impact on the environment and the quality of life of the surrounding community. The objective of this study is to provide organic waste treatment facilities that produce environmentally friendly products by applying the biophilic concept, thereby helping to reduce environmental pollution caused by improperly managed waste. The methods used in this research include a qualitative-descriptive approach through literature review, field observation, and site analysis. The results of the study indicate that the integration of biophilic elements such as natural lighting, cross ventilation, vegetation, and visual connections with nature can enhance user comfort and strengthen ecological awareness. Thus, the design of organic waste processing facilities that apply biophilic architectural principles has the potential to become an environmentally friendly and sustainable architectural solution in densely populated urban areas such as Pasar Kebayoran Lama. Keywords: Biophilic architecture; Kebayoran Lama; organic waste treatment; sustainable design; traditional market Abstrak Permasalahan lingkungan akibat penumpukan limbah organik, khususnya di kawasan pasar tradisional, menjadi isu krusial yang memerlukan solusi berkelanjutan. Peningkatan produksi limbah organik yang sangat signifikan terjadi di kawasan Pasar Kebayoran Lama dikarenakan kawasan padat aktivitas yang menghasilkan limbah organik dalam jumlah besar setiap harinya. Limbah organik sebagian besar disalurkan ke pembuangan akhir tanpa melewati proses yang efektif sehingga menambah beban lingkungan. Penelitian ini mengkaji penerapan konsep arsitektur biophilic pada fasilitas pengolahan limbah organik di kawasan Pasar Kebayoran Lama sebagai upaya menciptakan ruang pengolahan yang tidak hanya fungsional, tetapi juga memberikan dampak positif terhadap lingkungan dan kualitas hidup masyarakat sekitar. Studi ini bertujuan untuk adalah dengan menyediakan fasilitas pengolahan limbah organik yang akan menghasilkan produk ramah lingkungan dengan menerapkan konsep biophilic, untuk membantu mengurangi pencemaran pada lingkungan yang disebabkan oleh limbah yang tidak dikelola dengan baik. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif-deskriptif melalui studi literatur, observasi lapangan, dan analisis tapak. Hasil penelitian menunjukkan bahwa integrasi elemen-elemen biophilic seperti pencahayaan alami, ventilasi silang, vegetasi, serta hubungan visual dengan alam dapat meningkatkan kenyamanan pengguna dan memperkuat kesadaran ekologis. Dengan demikian, desain fasilitas pengolahan limbah organik yang menerapkan prinsip-prinsip arsitektur biophilic berpotensi menjadi solusi arsitektural yang ramah lingkungan dan berkelanjutan di kawasan urban padat seperti Pasar Kebayoran Lama.